Association between Vitamin D 1,25 (OH)2 D3 Serum with Endometriosis-Related Pelvic Pain and Infertility Condition in Endometriosis - Wiyasa, I Wayan Arsana; Suseno, Daniel Alexander; Suwana, Febie Putra (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Endometriosis is an estrogen-dependent chronic inflammatory disease characterized by the growth of endometrial tissues outside the endometrium or in the pelvic area. This condition is usually found in reproductive women, 15 – 49 years old. Chronic pelvic pain related to endometriosis is one of the major symptoms that makes women come to the clinic, besides dysmenorrhea and dyspareunia. This condition also affects the fertility of women, which, in some reports, shows that 30 – 50% women with endometriosis are also infertile. Vitamin D is a type of vitamin that is popular for treating reproductive problems. Vitamin D (1,25 (OH)2 D3) serum is important in inflammation and implantation, which supports overcoming endometriosis symptoms. Material and Methods: The Present study performed a cross-sectional study. A total of ninety-one women were included in this study, which was divided into three groups: normal group, the pelvic pain group, and the infertility pain. In this study, from ANOVA and confirmed with LSD 95% test. Results: There is a difference in Vitamin D (1,25 (OH)2 D3) serum level in the chronic pelvic pain group and/or infertility group. This significantly shows that there is a correlation between those variables. Conclusion: Sexual health is an important concern for patients with coronary artery disease. Some patients are symptomatic and have difficulty having sex. This study identifies specific issues that need to be addressed, especially convenient time, medication safety, and effective communication when providing sexual education.